Analisis Pengimplementasian Pendistribusian Berkas Rekam Medis Pasien Rawat Jalan Di Rumah Sakit X Bandung - Alya Nurul Maulani; Aura Nurzilal Ridwan; Meira Hidayati; Aris Susanto (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2021)
Medical records are an important part of the treatment of patient health, one form of service in each public health facilities is the distribution of medical record files. Based on research conducted at Hospital X Bandung, in the distribution of medical records the system used has not fully used electronic, the data entered into the application will then be searched manually by the officer for further medical record files distributed to each polyclinic concerned. The purpose of this study is to find out how the distribution of outpatient medical records at Hospital X Bandung using descriptive qualitative research methods that are research that aims to explain and describe the on distributing outpatient medical record documents with subjects in this study is an outpatient medical record document at Hospital X Bandung while the object in this study is the medical record officer in the distribution and filing. Thus, it can be concluded that the implementation of the distribution of medical record files has been quite effective and in accordance with the standard of time that has been set and Standard Operating Procedure that has been made despite some problems and constraints that always occur at the time of distribution of medical records, one of them is the application system used errors or buffering, the code on each polyclinic is sometimes confused with each other, but the officers can solve the problem.